Cerebral correlates of imitation of intransitive gestures: An integrative review of neuroimaging data and brain lesion studies. (December 2018) - Lesourd, Mathieu; Osiurak, François; Baumard, Josselin; Bartolo, Angela; Vanbellingen, Tim; Reynaud, Emanuelle
Highlights: Neuroimaging data and brain lesions concerning imitation of gestures are reviewed. Imitation of intransitive gestures activates a bilateral fronto-parietal network. More brain areas are involved in meaningless compared to meaningful gestures. The angular gyrus is particularly important for body part coding. These results question neuropsychological accounts on apraxia. Abstract: The aim of the present review is to investigate the cerebral correlates, more particularly the role of the parietal lobe, when imitating intransitive gestures, a task highly sensitive to apraxic errors. By providing an integrative review of functional imaging and brain lesion studies, we focused our attention on the meaning of gestures (meaningful and meaningless) and the body parts (finger and hand). We found that imitation of intransitive gestures is relying upon a bilateral brain network including fronto-parietal areas irrespective of meaning or body parts. Moreover, we observed that while imitation of meaningful and meaningless gestures is predominantly impacted following left parietal lesions, more brain areas are engaged during meaningless gesture imitation. Concerning body parts, whereas imitation of hand postures is relying upon the left parietal lobe (angular gyrus), imitation of finger postures is more likely to be impaired following lesions in the frontal lobe, insula and basal ganglia. These results question neuropsychological theories on apraxia and open promising avenues for a better understanding of apraxia.